PENAMBAHBAIKAN SKEMA EULER MENGGUNAKAN KONSEP MIN DAN PENGUJIAN KE ATAS PERSAMAAN LITAR PERINTANG ARUHAN (RL) - Nooraida Samsudin (Tesis, 2020)
This study aims to develop a new Modified Euler method which incorporates the concept of original Modified Euler method and mean. The proposed method is tested in the First-Order Equation (ODE) by taking maximum error value.